Physico-chemical-anatomical aspects of Liquidâmbar wood for the pulp and paper production - Vivian, Magnos Alan; Castro, Amanda Fernandes de; Modes, Karina Soares; Morais, Weslley Wilker Corrêa; Silva Júnior, Francides Gomes da (Revista de Ciências Agroveterinárias, 2023)
The pulp and paper sector has a notable highlight in the Brazilian economy, contributing significantly to the trade balance, job creation and investments. Currently, the sector basically uses wood from two genus to produce pulp for the short fiber and long fiber segments, Eucalyptus and Pinus, respectively. However, it’s essential to study new raw materials, which may arise as an alternative to those already consolidated. In this sense, the objective is to evaluate the properties of Liquidambar styraciflua wood for the pulp and paper production. For this, five 7-year-old trees were used, from which discs were extracted along the trunk to evaluate the basic density, chemical composition and morphology of the wood fibers. The mean and weighted basic density values obtained for L. styraciflua wood were 0.482 and 0.484 g/cm³, respectively, which allowed classifying it as medium density, a value close to that of other hardwood species used for pulp production. Regarding the chemical composition, low levels of ash (0.29%) and lignin (24.71%) and high levels of holocellulose (70.88%) and extractives (4.40%) were observed. As for the morphological characterization of the fibers, the mean values of length of 1.82 mm, width of 27.84 μm, lumen diameter of 16.10 μm and wall thickness of 5.87 μm were observed. In addition, mean values of 42.60%, 57.40%, 0.77 and 65.22 were obtained for the parameters of wall fraction, flexibility coefficient, Runkel index and felting index, respectively. In general, based on the physical-chemical-anatomical characteristics obtained for the L. styraciflua wood, it’s concluded that it has aptitude for the pulp and paper production.